Rencana Anggaran Biaya (RAB) pada pembangunan Mesjid berdasarkan Harga Satuan Standar Provinsi Sumatera Utara - Nasution, Adinda Juwita (universitas teuku umar, 2023)
The construction of a mosque requires careful budget planning so that the project can run smoothly and follow expectations. One of the critical steps in budget planning is to prepare a Cost Budget Plan (RAB) that is accurate and follows the unit price standards applicable in the area. This journal aims to present the RAB on the construction of mosques based on the Standard Unit Price of North Sumatra Province. This study's standard unit price data were obtained from official government sources and related institutions. The methodology used in this study includes field surveys, unit price data collection, and budget planning analysis. Field surveys were conducted to identify the needs of mosque construction and get a clear picture of the required specifications. Unit price data on building materials, construction work, and labour are obtained from reliable sources. Next, a budget planning analysis is carried out to calculate the estimated total cost of the mosque construction project. The results showed that the RAB on the construction of mosques based on the Standard Unit Price of North Sumatra Province provides accurate cost estimates and can be used as a guide in budget planning. The RAB includes costs for building materials such as bricks, cement, sand, and concrete iron, construction work such as installing roofs, floors, and walls, and the labour required in the construction process. This research is expected to contribute to the budget planning of mosque construction in North Sumatra and become a reference for parties involved in similar projects. By having an accurate RAB, it is hoped that the mosque's construction can run smoothly and efficiently per the plan set.